Protocolized approach saves the limb in peripheral arterial injury: A decade experience - Pratyusha Priyadarshini; Supreet Kaur; Komal Gupta; Abhinav Kumar; Junaid Alam; Dinesh Bagaria; Narender Choudhary; Amit Gupta; Sushma Sagar; Biplab Mishra; Subodh Kumar (Chinese Journal of Traumatology)
Purpose: Outcomes of peripheral arterial injury (PAI) depend on various factors, such as warm ischemia time and concomitant injuries. Suboptimal prehospital care may lead to delayed presentation, and a lack of dedicated trauma system may lead to poorer outcome. Also, there are few reports of these outcomes. The study aims to review our experience of PAI management for more than a decade, and identify the predictors of limb loss in these patients. Methods: This is a retrospective analysis of prospectively maintained database of trauma admissions at a level I trauma center from January 2008 to December 2019. Patients with acute upper limb arterial injuries or lower limb arterial injuries at or above the level of popliteal artery were included. Association of limb loss with ischemia time, mechanism of injury, and concomitant injuries was studied using multiple logistic regressions. Statistical analysis was performed using STATA version 15.0 (Stata Corp LLC, Texas). Results: Out of 716 patients with PAI, the majority (91.9%) were young males. Blunt trauma was the most common mechanism of injury. Median ischemia time was 4 h (interquartile range 2–7 h). Brachial artery (28.5%) was the most common injured vessel followed by popliteal artery (17.5%) and femoral artery (17.3%). Limb salvage rate was 78%. Out of them, 158 (22.1%) patients needed amputation, and 53 (7.4%) had undergone primary amputation. The majority (88.6%) of patients who required primary or secondary amputations had blunt trauma. On multivariate analysis, blunt trauma, ischemia time more than 6 h and concomitant venous, skeletal, and soft tissue injuries were associated with higher odds of amputation. Conclusion: Over all limb salvage rates was 77.9% in our series. Blunt mechanism of injury and associated skeletal and soft tissue injury, ischemia time more than 6 h portend a poor prognosis. Injury prevention, robust prehospital care, and rapid referral to specialized trauma center are few efficient measures, which can decrease the morbidity associated with vascular injury.